Reducing the unmet needs of family planning among women of reproductive age in Northern Region of Ghana - Hikimatu Tuntei-ya Mohammed; Zaffar Ullah (Universitas Aisyiyah Yogyakarta, 2020)
The recent Ghana Demographic and Health Survey 2014, estimated that 30 % of currently married women have an unmet need for family planning services, with 17% having an unmet need for spacing and 13% having an unmet need for limiting. The objective of the study was to review the unmet need of family planning in order to make appropriate recommendation to improve family planning use in the Northern Region of Ghana. A conceptual framework which outlines the factors that interplay to determine the use of family planning services in Northern Region of Ghana was designed and used for the study. The data were sought from unpublished documents from the Regional Health Directorate of Northern Ghana, websites of Ghana Health Service, online international publications and University of Leeds Library. The unmet needs of family planning in the region was found to result from a number of factors including inaccessibility to family planning services, non-availability of some type of contraceptive methods in the communities, religious beliefs that contradict the use of family planning, traditional and cultural belief system which promotes high fertility preferences, high illiteracy level, non-approval of family planning by men who are the decision makers, misconception about the use of contraception and high poverty in the region. The identified possible strategies for tackling the factors responsible for unmet need of family planning in the Northern Region, community-based family planning services, family planning health education outreach, peer education and religious-based education were found to be considerably effective, feasible and sustainable.